Assessing the Great Resignation phenomenon: voluntary resignation of young Italian workers during the COVID19 pandemic - Borrelli, I.; Santoro, P. E.; Gualano, M. R.; Moscato, U.; Rossi, M. F. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
reported increase in voluntary resignation from employment at a global level, especially among the youngest workers. The aim of this study is to investigate the social, demographic, and cultural characteristics of young people aged between 25 and 45 years who voluntarily resigned from their previous jobs during the COVID-19 pandemic.Methods. This is a cross-sectional observational study; an ad hoc questionnaire was designed and administered via an online link. Descriptive analyses were performed to describe the sample, and the Pearson analysis was performed to investigate statistically significant correlations; p values ≤ 0.05 were considered statistically significant.Results. A total of 72 valid responses were gathered. Mean age was 32.6 years; 43.1% participants were males, 54.2% were married, and 80.6% had no children; most participants (68.1%) had a college level education. The most reported cause of job resignation was work dissatisfaction (38.9%), followed by inadequate remuneration (27.8%). The most reported perspective for people who had resigned or were planning on resigning, was a better salary (27.8%), followed by the pursuit of a higher work-life balance (25.0%). The perception that having resigned was the right choice was significantly correlated with the timeframe of resignation (p